Incompatible type A plasma transfusion in patients requiring massive transfusion protocol: Outcomes of an Eastern Association for the Surgery of Trauma multicenter study. Issue 1 (July 2017) - Stevens, W. Tait; Morse, Bryan C.; Bernard, Andrew; Davenport, Daniel L.; Sams, Valerie G.; Goodman, Michael D.; Dumire, Russell; Carrick, Matthew M.; McCarthy, Patrick; Stubbs, James R.; Pritts, Timothy A.; Dente, Christopher J.; et al.
Abstract : ABSTRACT: With a relative shortage of type AB plasma, many centers have converted to type A plasma for resuscitation of patients whose blood type is unknown. The goal of this study is to determine outcomes for trauma patients who received incompatible plasma transfusions as part of a massive transfusion protocol (MTP). METHODS: As part of an Eastern Association for the Surgery of Trauma multi-institutional trial, registry and blood bank data were collected from eight trauma centers for trauma patients (age, ≥ 15 years) receiving emergency release plasma transfusions as part of MTPs from January 2012 to August 2016. Incompatible type A plasma was defined as transfusion to patient blood type B or type AB. RESULTS: Of the 1, 536 patients identified, 92% received compatible plasma transfusions and 8% received incompatible type A plasma. Patient characteristics were similar except for greater penetrating injuries (48% vs 36%; p = 0.01) in the incompatible group. In the incompatible group, patients were transfused more plasma units at 4 hours (median, 9 vs. 5; p < 0.001) and overall for stay (11 vs. 9; p = 0.03). No hemolytic transfusion reactions were reported. Two transfusion-related acute lung injury events were reported in the compatible group. Between incompatible and compatible groups, there was no difference in the rates of acute respiratory distress syndrome (6% vs. 8%; p = 0.589), thromboembolic events (9% vs. 7%; p = 0.464), sepsis (6% vs. 8%; p = 0.589), or acute renal failure (8% vs. 8%, p = 0.860). Mortality at 6 (17% vs. 15%, p = 0.775) and 24 hours (25% vs. 23%, p = 0.544) and at 28 days or discharge (38% vs. 35%, p = 0.486) were similar between groups. Multivariate regression demonstrated that Injury Severity Score, older age and more red blood cell transfusion at 4 hours were independently associated with death at 28 days or discharge; Injury Severity Score and more red blood cell transfusion at 4 hours were predictors for morbidity. Incompatible transfusion was not an independent determinant of mortality or morbidity. CONCLUSION: Transfusion of type A plasma to patients with blood groups B and AB as part of a MTP does not appear to be associated with significant increases in morbidity or mortality. LEVEL OF EVIDENCE: Therapeutic study, level IV.